Model Perlindungan Korban Tindak Pidana Kesusilaan Terhadap Anak Dalam Perspektif Hukum Pidana Di Indonesia (Studi Kasus Pada Yurisdiksi Hukum Kabupaten Sragen) - Prawati, Ratna, Prof. Dr. Khudzaifah Dimyati, S.H., M.Hum, Dr. Natangsa Surbakti, S.H., M.Hum (2015)
Decency criminal cases experienced by the children, from time to time increase. It is very alarming. The number of rape cases that occurred in Sragen figures show quite astonishing. Throughout the past year, the number of rapes and molestation jumped nearly 100 percent, or doubled. violence and rape and molestation has increased sharply from 2010 to 2011. Where in 2010 there were only 36 cases in 2011 there were 60 cases or jumped close to 100 percent. And even more alarming, cases of violence and sexual offenses involving victims many minors. Based on the record, the number of victims of minors has increased nearly 200 percent. Therefore, efforts are required to realize the protection and welfare of children, to provide a guarantee of the fulfillment of their rights and the existence Of non- discriminatory treatment. The formulation of the problem which is the object of this study are: a) What is the position on the morality of crime victims in the child Sragen in victimology perspective?,What models and offer protection to victims of criminal acts of decency in children Sragen (includes rules and law enforcement agencies). This type of research in this study was descriptive using socio-juridical. The materials used are the analysis of secondary data in the form of regulations per - Law Invitations and data Sragen Court ruling law crime of morality in children from 2011 to 2013. The results of this research are as follows: (1) the legal protection for the child victim of sexual assault crime is important to be conducted considering that the position of children is vulnerable to the occurrence of crimes, particularly sexual assault crime. Children who actually become the victim of sexual assault crime need to be protected due to: (a) their weak physical aspect; (b) their condition which is still labil (c) their milieu; (d) their need for education; and (e) the impact of technological advancement on children; (2) the efforts to give legal protection to the child victim of sexual assault crime can be made in the forms of protection by law, protection during the criminal justice process, and protection from the society; (3) the models of legal protection ideal to be implemented to protect the child victim of sexual assault crime are made through the approaches, namely: (a) penal approach which takes the form of legislation with comprehensive regulation on the criminal victim; and (b) non-penal approach which takes the forms of cultural approach and moral/education approach.